Sickle cell anaemia in Cameroon : co-inheritance of α-thalassemia, HBB gene haplotypes, clinical & haematological characterisations - Rumaney, Maryam (Division of Human Genetics, 2015)
Background: Although sickle cell anaemia (SCA) is genetically characterised by a single point mutation, patients can manifest varying degrees of clinical severity due to various genetic modulators that affect the phenotype of this disease. The co-inheritance of alpha-thalassemia (α-thalassemia) has been associated with a milder phenotype in SCA patients (e.g. lower stoke rate), but could also result in the increase of vaso-occlusive (VOC) pain episodes. There is a scarcity of data on the co-inheritance of α-thalassemia and SCA in Cameroon. The present study explored the correlation between α-thalassemia, haematological indices, and clinical events in Cameroonian SCA patients. Materials and Methods: For this cross-sectional study, a full blood count and clinical phenotype profile was collected for 262 Cameroonian individuals. Restriction fragment length polymorphism - polymerase chain reaction (RFLP-PCR) was performed for the molecular diagnosis of SCA and for the study of the β-globin (HBB) gene cluster haplotypes. Multiplex Gap-PCR was performed to investigate the 3.7kb and 4.2kb α-thalassemia gene deletions.